Whether ovalbumin performs as a particulate or polymeric emulsifier is largely determined by pH. (June 2020) - Xu, Yan-Teng; Wang, Yu-Han; Chen, Fei-Ping; Tang, Chuan-He
Abstract: Although it has been recognized that the emulsifying properties of ovalbumin (OVA), an important glycoprotein in egg white, are affected by pH, its pH-dependent structural characteristics still remain undetermined. The work demonstrated that pH played a crucial role in the emulsification of OVA, as a polymeric or particulate emulsifier; and at pH below its isoelectric point, OVA acted as a particulate emulsifier, while at strong alkali pHs, it was more like a polymeric emulsifier. The structural and physicochemical properties of OVA at different pHs of 2.0–12.0 were first evaluated in terms of particle size (and morphology), ζ -potential, tertiary and secondary conformations, and solubility. The results indicated that at pH 3.0, OVA tended to form highly aggregated spheres with a strong structural integrity, while at pH 11.0, its structure became unfolded and flexible. The emulsification performance and interfacial stabilization of OVA at three selected pHs (3.0, 7.0 and 11.0) were evaluated on the emulsions at oil volume fractions of 0.3 and 0.8. It was demonstrated that in both the cases, aggregated OVA spheres at pH 3.0 exhibited much better emulsification performance and interfacial stabilization than OVA at pH 7.0, while the enhancement of conformation flexibility by increasing pH from 7.0 to 11.0 did not produce significant influence. The findings would be of great importance for extending the knowledge about the structural basis of the emulsification and interfacial behavior of OVA, as well as for guiding the development of food emulsion formulations with OVA or egg white as the emulsifier or stabilizer. Graphical abstract: Image 1 Highlights: The emulsification of ovalbumin (OVA) was highly dependent on the pH. OVA at pH 3.0 or 7.0 was a particulate emulsifer, while that at pH 11.0 was a polymeric emulsifier. The OVA spheres at pH 3.0 were demonstrated to be outstanding Pickering stabilizers. The emulsification of OVA was not related to its conformation flexibility. High internal phase emulsion gels could be efficiently stabilized solely by OVA at pH 3.0.